Návrh vytápění a větrání pro „Emotivní dům“ - Brázda, Jan (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2017)
Diplomová práce se zabývá návrhem vytápění a větrání pro Emotivní dům navržený autorem diplomové práce. V první části je představena stavba a stavební řešení. V další části výpočet tepelné ztráty a návrh teplovzdušného vytápění, včetně volby vzduchotechnické jednotky a návrhu potrubní trasy a uvedení použitých komponentů. Vdalší části je návrh vytápění pro koupelny, které je provedeno podlahovým vytápěním. A vytápění neobytných místností pomocí otopných těles. V závěru práce je uvedena volba zdroje tepla. Práce obsahuje i vyhotovené výkresy.

This master’s thesis deals with the design of the heating and ventilation system for the ‘Emotivní dům’ which was designed by the author of this thesis. The first part of the thesis provides an overview of the project and the architectural design of the house. In the next part, the calculation of the heat loss and the design of the heating and ventilation system is described. War-air heating/ventilation is used in in the habitable rooms of the house with the hydronic system utilized in other spaces. The floor heating is used in the bathrooms and the other non-habitable spaces, such as the garage, are heated with radiators. A natural gas boiler is used as a heat source for both space heating and domestic hot water heating. The thesis contains the floor plans of the house as well as technical drawings of the heating and ventilation system.
Heating and ventilation in the „Emotivní dům“
Keywords: Teplovzdušné vytápění; zpětné získávání tepla; tepelná ztráta; podlahové vytápění; otopná tělesa; Emotivní dům; pocit domova; Warm air heating; heat recovery; heat loss; underfloor heating; radiator; Emotional home; feeling home